2020
DOI: 10.1186/s12879-020-05620-4
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of novel coronavirus disease (COVID-19) among dental surgeons of Nepal: a nationwide study

Abstract: Background COVID-19 is an emerging respiratory disease caused by a novel coronavirus. There is not much evidence assessing the knowledge of dental surgeons regarding COVID-19. This study was conducted to assess the knowledge of COVID-19 among dental surgeons of Nepal. Methods A web-based cross-sectional study was conducted among registered dental surgeons of Nepal. Ethical approval was obtained. Consent was taken, and knowledge on COVID-19 was assessed via a pre-tested structured questionnaire using Google fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The resulting insights allow a deep understanding of barriers and enablers to implementation both on an emotional but also a factual level. Notably, our findings can be triangulated with those of quantitative evaluations (e.g., from surveys), which highlighted that knowledge on COVID-19 increased with time and was generally not the main barrier for ICM in more recent surveys; that the adoption of PPE varied widely and that some PPE, such as face shields and FFP2-masks, were not implemented regularly; that there was uncertainty regarding how to adapt practice infrastructure and organization to reduce infection risks and that, generally, the specific setting was associated with the implementation of measures [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Our study now adds insights as to why all these observations were made.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting insights allow a deep understanding of barriers and enablers to implementation both on an emotional but also a factual level. Notably, our findings can be triangulated with those of quantitative evaluations (e.g., from surveys), which highlighted that knowledge on COVID-19 increased with time and was generally not the main barrier for ICM in more recent surveys; that the adoption of PPE varied widely and that some PPE, such as face shields and FFP2-masks, were not implemented regularly; that there was uncertainty regarding how to adapt practice infrastructure and organization to reduce infection risks and that, generally, the specific setting was associated with the implementation of measures [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Our study now adds insights as to why all these observations were made.…”
Section: Discussionmentioning
confidence: 99%
“…While the knowledge on COVID-19 has increased over the course of the pandemic, the majority of dentists have not yet implemented all recommended measures. A few dentists aimed to exceed recommendations or legal minimum standards [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. It is, however, not clear why implementation differs between measures, dentists and settings.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the present study, the vast majority of pediatric dentists had a good level of knowledge about COVID-19 disease. Although questions evaluating the knowledge level of dentists might be different among studies, previous studies have also found that dentists have a good knowledge level as well [11,12,28,30,34,50]. The results of this study showed that the knowledge level of dentists about COVID-19 is sufficient, but it is recommended that information should be continuously updated in the following periods according to the course of the disease, in order to optimize the management of COVID-19.…”
Section: Discussionmentioning
confidence: 65%
“…The present study showed that 55% of all participants attended a webinar on COVID-19. Previous studies [2,11,13,20,[27][28][29][30][31][32] showed the various rates of attendance of dentists at an education program on COVID-19. Contrary to these results, some researchers reported insufficient training [12,14,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, during this crisis, more doubt and disagreement between professional have been noticed, mainly due to the level of knowledge and perceptions of DOHCWs toward COVID-19 remain unclear leading di cult for them to go further in crisis. Knowledge of disease may in uence clinicians' attitudes and practices, and incorrect attitudes and practices directly increase the risk of infection [53,54]. Knowledge about clinical features, pathophysiology, diagnosis and management help clinicians to recognize and handle COVID-19 patients, identify the high-risk dental procedure.…”
Section: Professional Impactsmentioning
confidence: 99%